Las contingencias del patrimonio artístico peruano - Tello, Martha Barriga (Revista VIS: Revista do Programa de Pós-Graduação em Artes Visuais, 2017)
The artistic cultural heritage from countries which were invaded or faced war in any time of their history has been subject to destruction or pillage. The modes in which that has occurred are varied and, frequently, involved their inhabitants and their testamentary donations. Among those cases are the Peru, in which the predation has started since the arrival of the European, in the sixteenth century and has followed a steady pace until the present. Here is a brief recount of the destination some ancient and viceregal Peruvian artworks and how their absence damages the national identity.